Investigating the dynamics of water and sediment disruption due to impeller action in silt-rich reservoir zones of inland waterways in China - Wang, Hao; Wang, Yu; Liu, Kaiqing; Luo, Tianfeng; Li, Jinping; Zhang, Ying; Miao, Tian; Tian, Miao; Wang, Zhehui; Zhang, Xiaolong (Frontiers in Earth Science, 2024)
To investigate the characteristics of sediment disturbance caused by impeller rotation in the reservoirs of inland rivers with high sediment content in China, a scaled experimental model was established in Lanzhou, Gansu Province, following the principle of similarity. This model reflects typical environmental conditions of inland water reservoirs in Northwest China. This study integrated numerical simulations performed using Ansys Fluent software and corroborated the findings through hydraulic experiments. Speculation suggests this method facilitates comparing the effects of impeller submersion depth, inflow velocity, and rotational speed on sediment-laden flow disturbance. Computational Fluid Dynamics (CFD) and the κ-ε Realizable model were adopted in the numerical simulation of the solid-liquid mixing process. These simulations were subsequently verified against the experimental model. The results indicated that impeller velocity gradually increased from 2 rad/s to 8 rad/s when immersed in the center of the flow field at a depth of 1000 mm, resulting in a higher rate of bottom sediment suspension.Additionally, the rate of suspended sediment discharge from the model outlet increased with the inflow velocity increasing from 0.1 m/s to 0.8 m/s. Furthermore, decreasing the impeller's submersion depth from 600 mm to 1200 mm reduces the maximum disturbance radius affecting the bottom sediment. The reliability of the simulation was confirmed by juxtaposing the software simulation results with experimental data. This study provides insights into the disturbance mechanisms of sediment-laden flows in the reservoir areas of inland rivers in China and lays the foundation for comprehensive sediment discharge explorations in these environments.